FEATURES OF THE ACCOUNTING OF FINANCIAL RESULTS AT AGRICULTURAL ENTERPRISES - Вікторія Гринь; Наталія Теліус (Економіка та суспільство)
The subject of the study is a set of theoretical, methodological and practical issues related to the formation, organization and creation of the most advanced accounting system of financial results, which ensures the improvement of the management efficiency of an agricultural enterprise. The purpose of writing this article is to substantiate certain theoretical and methodological provisions and develop practical recommendations for improving the accounting of financial results of activities for making managerial decisions regarding the development of agricultural production. The methods of logical analysis, induction and deduction are also applied to clarify the essence of income and financial results; methods of expert assessments – for researching the state of accounting in agricultural formations; methods of functional and logical analysis – for building an accounting information model of financial results.